2000
DOI: 10.1159/000017474
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Insulin-Induced Hypoglycemia on Fetal versus Adult Brain Fuel Utilization, Assessed by <sup>13</sup>C MRS Isotopomer Analysis of [U-<sup>13</sup>C]Glucose Metabolites

Abstract: Tight glycemic control during diabetic pregnancy has been shown to significantly reduce the occurrence of congenital malformations and other effects of maternal diabetes on the offspring. However, intensive insulin therapy often causes recurring acute maternal hypoglycemia, which has been found to be harmful to the developing fetus, although the mechanisms involved are not clear. The aim of our work was to study the effect of acute insulin-induced maternal hypoglycemia on glucose metabolism in the fetal brain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
1
3
1
Order By: Relevance
“…A slightly better chemical shift separation of glutamate C3 from the overlapping glutamine C3 was achieved at 11.7 Tesla as expected. In contrast to previous in vitro studies using [U-13 C]glucose with low fractional enrichment [14,[38][39][40], no significant singlets (e.g., Glu3S, Glu2S, Gln3S, Gln2S) were observed in the current study due to the use of close to 100% fractional enrichment of plasma [U-13 C]glucose. Due to large susceptibility effect in vivo, the spectral resolution achieved in this study is poorer than that obtainable in vitro.…”
Section: Discussioncontrasting
confidence: 99%
“…A slightly better chemical shift separation of glutamate C3 from the overlapping glutamine C3 was achieved at 11.7 Tesla as expected. In contrast to previous in vitro studies using [U-13 C]glucose with low fractional enrichment [14,[38][39][40], no significant singlets (e.g., Glu3S, Glu2S, Gln3S, Gln2S) were observed in the current study due to the use of close to 100% fractional enrichment of plasma [U-13 C]glucose. Due to large susceptibility effect in vivo, the spectral resolution achieved in this study is poorer than that obtainable in vitro.…”
Section: Discussioncontrasting
confidence: 99%
“…Instead, those studies suggested differences in brain oxidative metabolism, associated with the mitochondrial TCAc. Our estimations of the relative brain glucose fluxes through PDH, PC and ME were within the ranges reported (PC/PDH = 0.14±0.04 in control rabbit fetuses [27]; PC/ME = 0.28±0.09 in neurons and 0.46±0.18 in astrocytes of primary cell cultures from embryo and neonatal rat brains, respectively [28]) but no significant differences were detected either between FGR and AGA brains.…”
Section: Discussionsupporting
confidence: 86%
“…This assumption has no obvious foundation and may seriously underestimate the stoichiometry between oxidative glucose consumption and glutamate cycling. For example, if the rate of glutamine synthesis via the anaplerotic pathway during normal activity had been 30% of total glutamine synthesis, as others have observed (Kunnecke et al, 1993; Lapidot and Haber, 2000), then the stoichiometry between oxidative glucose consumption and glutamate cycling would be roughly 1.5:1 rather than 1:1 (estimated from Sibson et al, 1998). Thus, the stoichiometry between oxidative glucose metabolism and glutamate cycling may vary greatly depending on the assumptions used.…”
Section: Part Ii: Experimental Evidence Regarding Glucose and Lactatementioning
confidence: 90%